Analisis Determinan Audit Delay Perusahaan Property dan Real Estate - Harianto, Harianto; Saputra, Agung Joni (E-Jurnal Akuntansi; Vol 32 No 2 (2022), 2022)
One of the things that are mandatory for public companies is the obligation to report an annual audit report. The purpose of this study was to examine the effect of operating complexity, firm size, solvency, audit switching and profitability on Audit Delay. The companies studied came from the property and real estate sectors listed on the Indonesia Stock Exchange in 2018-2020 with a total sample of 52 companies. The analysis technique used is multiple linear regression. The results showed that firm size had no effect on Audit Delay, profitability had no effect on Audit Delay, solvency had no effect on Audit Delay, operating complexity had no effect on Audit Delay, audit switching had no effect on Audit Delay. Keywords: Company Size; Operational Complexity; Profitability; Audit Switching; Leverage; Audit Delay.